Assessing vaccine hesitancy using the WHO scale for caregivers of children under 3 years old in China - Man Cao; Jinhong Zhao; Cunrong Huang; Xianglin Wang; Lihong Ye; Xueyan Han; Wenzhou Yu; Zundong Yin; Juan Zhang; Yuanli Liu (Frontiers Media S.A., 2023)
IntroductionVaccine hesitancy may increase infectious disease burden and impede disease control efforts, while few studies have measured such a phenomenon with a standardized tool in China. This study aimed to test the validation of the Vaccine Hesitancy Scale (VHS) developed by the WHO SAGE Working Group among caregivers and examine demographic characteristics associated with caregiver hesitancy in six provinces of China.MethodsUsing a multistage sampling design, this study was conducted in 36 immunization clinics in six provinces from December 2019 to August 2020. Caregivers of children aged 0-3  years were included. The VHS was used to assess vaccine hesitancy. The construct validity and internal consistency of the scale were assessed. Associations between caregivers' characteristics and vaccine hesitancy were examined by simple and multiple linear regression models.ResultsOf the 3,359 participants included, a two-factor structure within the scale was identified, consisting of "lack of confidence" (1.89 ± 0.53) and "risks" (3.20 ± 0.75). Caregivers engaged in medical work expressed more confidence and were less concerned about risks compared to those of non-medical staff (p < 0.05). Participants with higher income levels were more confident (p < 0.05), while those surveyed after the COVID-19 pandemic, who were mothers, who had an older child, or who were raising a second or above birth child, had less concern about risks (p < 0.05).DiscussionWe found that the VHS had acceptable reliability and construct validity and caregivers' hesitancy was driven more by concerns about risks than by the lack of confidence. Countering these concerns will be particularly important among non-medical staff, lower income, child's fathers, having a younger child, or raising first-birth child groups.